PROPOSAL OF THE ENTRANCE FEE MODEL TO THE BUS TERMINAL (Perner's Contacts, 2009)
The article solves the problems of developing the model of the entrance fee on the bus terminal.
Keywords: Model; modelling; entrance fee; bus terminal